2023
DOI: 10.1177/1357633x231162399
|View full text |Cite
|
Sign up to set email alerts
|

The use of telemedicine for perioperative pain management during the COVID-19 pandemic

Abstract: Introduction Using a human factors engineering approach, the Johns Hopkins Personalized Pain Program adopted telemedicine for perioperative pain management in response to the COVID-19 pandemic. This study examines the impact of telemedicine adoption on the quality and outcomes of perioperative pain management. Methods A mixed-methods study with a convergent parallel design was conducted. From June 2017 to December 2021, 902 patients participated in the Personalized Pain Program. Quantitative data on daily opio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…We have previously demonstrated that transitional perioperative pain services have the potential to facilitate opioid reductions during treatment [34][35][36]57]. To our knowledge, this is the first study to report sustained reductions in opioid use, in terms of the number of participants who discontinued opioids and mean opioid doses, nearly three years after initiating treatment in a transitional perioperative pain service.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…We have previously demonstrated that transitional perioperative pain services have the potential to facilitate opioid reductions during treatment [34][35][36]57]. To our knowledge, this is the first study to report sustained reductions in opioid use, in terms of the number of participants who discontinued opioids and mean opioid doses, nearly three years after initiating treatment in a transitional perioperative pain service.…”
Section: Discussionmentioning
confidence: 71%
“…These interviews were conducted with participants who were initially seen prior to the COVID-19 pandemic. The PPP transitioned to telemedicine services in March 2020 [78]; ongoing studies are evaluating how this transition has impacted clinical outcomes [57] and patients' experiences in the PPP.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that PPP patients who were using opioids preoperatively achieve significant postoperative reductions (from 81 to 29 mg, P < .001) in daily opioid use. 8 Furthermore, via self-reported outcome measures, patients report significant reductions in pain severity and pain interference, as well as improved physical functioning. 8 Approximately 60% of patients discontinue opioids by PPP discharge, and those who successfully complete the program remain abstinent or on low doses (<30 mg) of morphine equivalent doses up to 2 years after PPP discharge (unpublished data).…”
Section: Outcomes Of the Pppmentioning
confidence: 99%